Development of e-worksheet discovery learning teaching materials assisted by liveworksheet on virus material - Susi Helen Christin; Eko Sri Wahyuni; T. Titin (Research and Development in Education (RaDEn), 2025)
This research is motivated by the conditions in the field obtained information that the worksheet used does not yet have the syntax of the learning method and only contains work steps. Hence, students are less motivated in the learning process. This study aims to determine the feasibility and response of students to e-worksheet discovery learning teaching materials assisted by liveworksheets on virus material. The type of research used is development research using the ADDIE development model, namely analysis, design, and development. Data collection techniques in the study were interviews, e-worksheet product validation sheets, and student response questionnaires. The validation instrument uses a Likert scale. The research subjects consisted of 15 students. Based on data analysis, e-worksheet discovery learning product validation results obtained a score of 0.88 with a valid category. In contrast, e-worksheet discovery learning product reliability results obtained a score of 0.726 with moderate reliability. The overall average results of students' responses to e-worksheet discovery learning on virus material is 84.58% with an outstanding category, so it can be concluded that e-worksheet discovery learning teaching materials on virus material are valid and feasible.